Fratture del femore prossimale - Capuano, N.; Carbone, F.; Del Buono, A. (Lo Scalpello - Journal, 2018)
PROXIMAL FRACURES OF THE FEMURThe goals of a tissue-preserving minimally invasive approach to the hip are to provide early short term recovery,achieve hip joint stability, minimise muscle strength loss from surgery, spare the peri-articular soft tissues, and allowfor unrestricted motion in the long term. It is indicated in case of hip arthroplasty in patients with no pre-existinghardware, with a sufficient space between the acetabular rim and greater trochanter, and for the management ofsubcapital femoral fractures in older patients. Contraindications include protrusio acetabuli and joint stiffness.Starting from a lateral position, a 5–8 cm incision is made from the tip of the greater trochanter, followed byidentification and transaction of the piriformis tendon. Anterior mobilization of the gluteus minimus follows, togetherwith exposure and capsulotomy of the posterior superior of the capsule. We proceed then to prepare the acetabulum.After removal of the head and neck, we prepare the femoral canal. Complete muscle relaxion is helpful to proceed tosatisfactory trial reduction. As regards postoperative management, patients may progress to motion and weightbearing without restriction. From April 2009 to December 2016, the first author (NC) operated on 820 patients forsubcapital fractures of the femoral neck. Seven hundred (85%) patients could walk with full weight load within 24hours from the operation, and climb stairs 24 hours later with low loss of blood, and fast recovery.